Perturbation effects in men`s and women`s international sevens - Barkell, J. F.; O'Connor, D.; Cotton, W. G. (International Journal of Performance Analysis in Sport, 2017)
Understanding how to effectively perturb the defence in sevens rugby is essential for tactical preparation. The aim of this study was to (a) identify any commonly occurring forms of perturbations; (b) gain an understanding of how, when and where perturbations are occurring; and (c) whether certain forms of perturbations are more likely to create scoring plays and lead to success. Footage of 117 men`s games and 65 women`s games were analysed. From the selected games a total of (N = 1101) perturbations were recorded in the men`s competition and (N = 601) were recorded in the women`s competition. Comparisons between winning and losing teams were examined through a series of Wilcoxon Signed Rank Tests (p < 0.05). Chi Square tests of Independence were also conducted to identify any associations between variables. Results identified differences between winning and losing teams in the number of perturbations and line breaks, tries from perturbations and the percentage of perturbations converted into tries. Evasive footwork in the middle of the field was the most commonly occurring perturbation type. Variations were evident between quarters and tries were associated with perturbations created closer to the attacking try line. It was identified that perturbations are associated with success for both men`s and women`s teams.